Evaluation of the coffee seeds viability by exudates - Sera, Gustavo Hiroshi; Miglioranza, Édison; Sera, Tumoru (Semina: Ciências Agrárias, 2006)
A quick evaluation of the germination quality of the seeds is very important for coffee growers. The aim of this research was to estimate the correlation coefficient between the germination and the liberation of brown exudates of coffee seeds with different times after preparation. Petri dishes and humid filter were used to place the seeds. The seeds were obtained from lots of seeds with several aging degrees. The experimental design used was in randomized blocks with seven replications and plots constituted by 10 seeds. High negative correlations (P=0.01) were obtained between the germination and germinative vigour with the liberation of brown exudates at different times. The variance analyses indicated significant differences to germination among seeds of different aging degrees at different evaluation times. The advantage of this technique is to evaluate the germinative quality in six or twelve hours, without the use of specialized labour and expensive equipments.